Photobiomodulation and Its Therapeutic Potential in Sleep Disturbances - Jieun Jung; Tae Kim (Sleep Medicine Research)
Photobiomodulation (PBM) is a non-invasive therapeutic technique employing specific wavelengths of red and near-infrared light to induce photochemical reactions in biological tissues without generating significant heat. PBM operates at low power densities, primarily acting through mitochondrial chromophores like cytochrome c oxidase to enhance cellular metabolism, energy production, and repair mechanisms. Based upon this foundational understanding, a critical evaluation was conducted to assess its impact on sleep-wake regulation. Current scientific evidence from both preclinical and clinical research suggests that PBM has the potential to influence sleep architecture, duration, and quality through complex interactions with cellular metabolic pathways and neurophysiological mechanisms governing the sleep-wake cycle. Despite growing scientific interest, significant research gaps persist; elucidating the precise cellular and molecular mechanisms by which PBM affects sleep physiology remains a primary challenge. There is an urgent need to standardize intervention protocols, including determining optimal wavelengths, dosage parameters, treatment durations, and delivery methods, to ensure consistent and reproducible results. Future research should focus on identifying predictive biomarkers for personalized treatment, examining transcranial PBM’s effects on neural pathways involved in sleep regulation, and assessing long-term safety to address potential cumulative effects. In conclusion, while PBM shows promise as a non-invasive therapeutic approach for sleep regulation, rigorous research is needed to establish its clinical efficacy and understand its molecular mechanisms, ultimately advancing it from an experimental therapy to a standardized treatment for sleep disorders.